Natural enemy release or biotic resistance? Insect herbivores associated with the exotic Solanum viarum (Solanaceae) and a sympatric native congener in KwaZulu-Natal, South Africa: Insect herbivores associated with Solanum viarum and Solanum dasyphyllum - Olckers, Terence; Msele, Kwanele; Egli, Daniella (African Entomology, 2024)
Native to South America, Solanum viarum Dunal (tropical soda apple; Solanaceae) is naturalised in several countries globally. The plant is a major invader in the southern USA, but has minor weed status in South Africa. We investigated whether S. viarum has escaped natural enemy pressure or has recruited insect herbivores from the local Solanum flora, which are exerting some level of biotic resistance. Insect species richness and abundance and the resulting levels of herbivory were compared between plants from sympatric populations of S. viarum and the native Solanum dasyphyllum Schumacher and Thonning in the KwaZulu-Natal Midlands. Foliage, floral material, and fruits were collected across seasons from 20 plants of each species and assessed in the laboratory. Despite no significant differences between the two species in the size of the sampled plants, S. viarum displayed significantly lower insect herbivore diversity and abundance and suffered significantly lower levels of damage to its photosynthetic and reproductive tissues. Five of the 11 specialist herbivore species recorded on S. dasyphyllum were associated with S. viarum, but in substantially lower numbers and in fewer samples. The flowerbud-galling moth Scrobipalpa sp. (Gelechiidae), which prevents fruiting in S. dasyphyllum, was absent on S. viarum and indicative of the negligible floral damage on S. viarum. Although the fruit of S. viarum were occasionally utilised by specialist herbivores, seed damage was similarly negligible. Due to its release from specialist natural enemies and with no evidence of biotic resistance, S. viarum may increase in weed status in South Africa.